Financial Literacy, Financial Education and Financial Experience: Conceptual Framework - Chabaefe, Nancy Neoyame; Qutieshat, Abubaker (International Journal of Economics and Financial Issues, 2024)
Low levels of financial literacy continue to persist around the world with women, the poor, lowly educated groups and the youth possessing the least levels of financial literacy. Research has shown that both financial education and financial experience can help boost levels of financial literacy. Despite this, there remains no conceptual framework that shows how financial education and financial experience can be used to boost levels of financial literacy. The purpose of this study is to propose a conceptual framework that links financial literacy, financial education, and financial experience. This paper is based on a literature review of journals on financial literacy, financial education, and financial experience that were published on both Google Scholar, Semantic Scholar, and Scopus from 2018 to 2023. Variables that emerged from the literature review were used to construct a conceptual framework. The findings of this study reveal that financial education and financial experience can be used to enhance financial literacy levels. Thus, it can be concluded that both financial education and financial experience can help to improve levels of financial literacy among individuals and various groups.